ANALISIS VARIABEL MAKROEKONOMI TERHADAP INDEKS SAHAM SYARIAH INDONESIA DENGAN METODE PENDEKATAN VECTOR AUTOREGRESSION - Muhammad Nasir; Fakriah Fakriah; Ayuwandirah Ayuwandirah (Politeknik Negeri Lhokseumawe, 2016)
This study will use empirical testing of the influence of variables of inflation, BI rate, exchange rate,money supply with Shari'ah Indonesia Stock Index. To see that effect will be made by the tests instages Vector Autoregression. Data are obtained from the monthly time series data issued by BankIndonesia, between the period January 2011 to December 2014. This study will use the unit root testby using Augmented Dickey Fuller (ADF), this test indicates the data is stationary and non-stationaryon the first level differense test. On the cointegration test against variables are co integration andlong-term relationship between the variables related and linked only in one direction only. So theneed to proceed with further testing using VECM. ISSI short-term models affected by inflation and theMoney Supply (JUB) at 90% confidence level. ISSI is affected inflation in the first lag significantlyaffect Indonesia Stock Index Shari'ah. ISSI also affected by the lag JUB 2.Keywords: Vector Autoregression, Augmented Dickey Fuller (ADF), stasioneritas, first difference,Kointegrasi, VECM